2018
DOI: 10.1590/1980-549720180001
|View full text |Cite
|
Sign up to set email alerts
|

Anemia e fatores associados em mulheres de idade reprodutiva de um município do Nordeste brasileiro

Abstract: ABSTRACT:Objective: To identify the prevalence of iron-deficiency anemia and associated factors in women at reproductive age in the city of Vitoria de Santo Antão, Pernambuco. Methods: Cross-sectional study with a representative sample of 322 women aged between 15 and 49 years. Anemia was diagnosed by measuring hemoglobin below 12 g/dL. The independent variables were: demographic and socioeconomic conditions (age, race/color, education, literacy, presence of children aged < 5 years in the household, regime of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
1
10
0
12
Order By: Relevance
“…A population-based study in Brazil with children and women of childbearing age also found higher prevalence of anemia in the Northeast Region 7 , indicating a relationship between anemia and socioeconomic and cultural conditions. Studies have also shown that people with poorer socioeconomic status and lower education are more likely to have anemia because of poor access to adequate and varied food 10,11,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A population-based study in Brazil with children and women of childbearing age also found higher prevalence of anemia in the Northeast Region 7 , indicating a relationship between anemia and socioeconomic and cultural conditions. Studies have also shown that people with poorer socioeconomic status and lower education are more likely to have anemia because of poor access to adequate and varied food 10,11,29 .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, data from the National Child and Women's Demographic and Health Survey (Pesquisa Nacional de Demografia e Saúde da Criança e da Mulher -PNDS) 2006 show that 29.4% of women aged 15 to 49 years had anemia, while the prevalence in children was 20.9% 7 . Studies with the female population of childbearing age reveal anemia prevalence ranging from 18.6% in women in the municipality of Pernambuco 11 to 38.0% in indigenous women 12 . In pregnant women users of Basic Health Units of Maceió, the prevalence was 28.3% in 2014 13 .…”
Section: Palavras-chavementioning
confidence: 99%
“…Os resultados apresentados também apontam para a carência de ferro na dieta baseada em itens da cesta básica, em comparação às re-comendações nutricionais atuais para mulheres em idade fértil. No contexto da saúde pública, verifica-se relevante papel da ingestão de ferro na prevenção da anemia ferropriva e ferropênica entre mulheres em idade reprodutiva e gestantes, grupos vulneráveis à ocorrência da deficiência nutricional 21,22 .…”
Section: Discussionunclassified
“…Teniendo un grupo etario más amplio, mujeres no embarazadas entre 15 y 49 años Habib et al reportan en Pakistán una prevalencia de anemia ferropénica de 18.1% (18) . En mujeres premenopáusicas de 15 a 50 años en Brasil se ha reportado una prevalencia de anemia por deficiencia de hierro de 18.6% (19) . En India se ha reportado una prevalencia de 44.0%, en Bangladesh Shill et al ,de 63.3% (20) .…”
Section: Materiales Y Métodosunclassified